Eight prehilar branches of the right renal artery - Nayak, Satheesha B. (Korean Association of Anatomists, 2014)
Imaging technology with its advancement in the field of urology is the boon for the patients who require minimally invasive approaches for various kidney disorders. These approaches require a precise knowledge of the normal and variant anatomy of vessels at the hilum of the kidney. During routine dissections, a variation in the branching pattern of the right renal artery was noted in an adult male cadaver. The right renal artery divided into upper and lower divisions 6cm away from the hilum of the kidney. The upper division gave 4 branches, and the lower division gave two branches. These two branches further bifurcated and gave 2 branches each. Thus, there were 8 prehilar branches of renal artery. The multiple prehilar branches led to a congested atmosphere at the hilum of the kidney. This arterial congestion might result in hindering the blood flow at the renal hilum. Apart from this, it might cause difficulties in diagnostic and therapeutic invasive procedures. Knowledge of this variation is of importance to radiologists and urologists in particular.